THE MINIMALLY INVASIVE METHODS OF TREATMENT OF ANTERIOR URETHRA STRICTURES - V. L. Medvedev; Y. N. Medoev; V. V. Mitusov (Вестник урологии)
This review is to evaluate literature concerning different methods of treatment of anterior urethra strictures: internal optical urethrotomy (OIU), laser urethrotomy, urethra stenting, urethra dilatation, OIU in combination with selfdilatation, OIU combined with chemicals injection. Evaluation of expedience, advisability and reasonableness of the chosen methods and techniques. Hereby presented statistical assessment of longtime postoperative data, low efficiency researches analysis. This research is compiled using Medline, PubMed and Embase databases.